PROBLEMATIKA HUKUM TERHADAP PRAKTIK TYING PADA PENJUALAN MINYAK GORENG MINYAKITA DI SAMARINDA - Arafah, Andi Zohrah Zahiroh; Arifudin, Nur; Pribadi, Deny Slamet (Jurnal Ilmiah Advokasi, 2025)
This study examines the practice of tying in the sale of the government-subsidized cooking oil "Minyakita" in Samarinda, where consumers are required to purchase additional products alongside the oil. Such practices violate Article 15(2) of Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. Using doctrinal legal research, the study identifies strong indicators of tying practices initiated by major distributors and continued by retailers, resulting in consumer disadvantage. The government and the Indonesian Competition Commission (KPPU) have implemented monitoring and educational measures, and are authorized to impose administrative sanctions or pursue criminal penalties. These findings highlight the importance of enforcing competition law in the distribution of essential goods.Keywords: Business Competition, Minyakita, Tying Sales